Effect of Relocation on Neuropsychiatric Symptoms in Elderly Adults Living in Long‐Term Care. Issue 11 (8th October 2018) - Haddad, Kamal El; de Souto Barreto, Philipe; Gerard, Stephane; Prouff, Aurelie; Vellas, Bruno; Rolland, Yves
Abstract : OBJECTIVES: To determine the evolution of behavioral and psychiatric symptoms of dementia (BPSD) in nursing home (NH) residents after an environmental change through a relocation to a more architecturally suitable facility, while conserving the same medical staff. DESIGN: Prospective, single arm study. SETTING: Long‐term care unit. PARTICIPANTS: NH residents (N=116; median age 82.3, range 75.5–89.2; median Neuropsychiatric Inventory for the Nursing Home (NPI/NH) score 22, range 11–34.5; 66.3% female), of whom 102 lived in regular units and 14 in specialized care units (SCUs). MEASUREMENTS: Neuropsychiatric symptoms were evaluated as part of a comprehensive geriatric assessment for each resident 1 week before the relocation and 3 times after the relocation (1, 4, 12 weeks) using the NPI/NH. RESULTS: A mixed‐effect linear model found no significant change in global NPI/NH score in the regular unit and a significant decrease in overall NPI/NH score 4 weeks after relocation in the SCUs (β‐coefficient for time by SCU=–11.5, 95% confidence interval (CI)=−17.9–5.2, p < .001), reaching a total decrease of 13 points by 12 weeks after relocation (β‐coefficient for time by SCU=–12.8, 95% CI=−19.1–6.4, p < .001). A statistically significant decrease of 3 points for disinhibition, apathy, and agitation accompanied the NPI/NH score in the secured unit. An increase of 3 points in aberrant motor behavior was seen by 12 weeks after relocation in the SCU. CONCLUSION: Relocation to an architecturally different facility significantly reduced BPSD of NH residents 1 month after relocation.J Am Geriatr Soc 66:2183–2187, 2018.